Strategi Fintech Syari'ah di Toko Elektronik Sunanti - Hernawati, Rita (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Sharia fintech is a technology-based financial solution that integrates sharia principles, such as the prohibition of usury, gharar, and maisir. The use of sharia fintech in Indonesia is growing, especially in supporting micro, small, and medium enterprises (MSMEs). Sunanti Electronics Store, which serves the majority of Muslim consumers, has the potential to utilize sharia fintech to increase its sales. This study aims to analyze the strategy of implementing sharia fintech in increasing sales at Sunanti Electronics Store. The method used is a descriptive-analytical approach with literature reviews and secondary data. The results of the study indicate that the implementation of sharia fintech through the murabahah financing scheme, sharia e-wallet, and sharia crowdfunding can increase customer loyalty, expand market reach, and create operational efficiency. However, the challenges faced include the lack of sharia financial literacy and limited digital infrastructure. For this reason, cooperation with sharia fintech providers and education for consumers are needed so that this implementation can run optimally. Sharia fintech is not only a transaction tool, but also an effective business strategy to increase competitiveness and business growth based on Islamic values.